2009
DOI: 10.1128/jcm.00353-09
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of a New Tetratrichomonas Species in a Patient with Empyema

Abstract: A new Tetratrichomonas species was identified by molecular and phylogenetic approaches in the pleural fluid from a patient with encysted empyema leading to dyspnea. This observation raised the questions of the real prevalence of pulmonary trichomonosis in humans, the zoonotic potential of trichomonads, and the existence of human-host-adapted strains. CASE REPORTA 40-year-old woman was admitted to the emergency unit with a bacterial infection and a history of fever, fatigue, vomiting, and respiratory distress f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 20 publications
1
28
0
2
Order By: Relevance
“…Not only between animals, but also for humans. Several reports in the literature suggest respiratory and intestinal infections in humans by these two etiologic agents (Jongwutiwes et al 2000, Kutisova et al 2005, Duboucher et al 2006, Mantini et al 2009). Considering these findings, these species should be carefully monitored as a question of public health in humans and domestic animals, related potential from the viewpoint of zoonotic transmission and poorly studying pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Not only between animals, but also for humans. Several reports in the literature suggest respiratory and intestinal infections in humans by these two etiologic agents (Jongwutiwes et al 2000, Kutisova et al 2005, Duboucher et al 2006, Mantini et al 2009). Considering these findings, these species should be carefully monitored as a question of public health in humans and domestic animals, related potential from the viewpoint of zoonotic transmission and poorly studying pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…A 50-ml sample of purulent fluid was characterized by a pH of 6.8, a lactate dehydrogenase (LDH) level of 1,320 IU/liter, a WBC count of 10,840 cells/l (96% neutrophils), high triglyceride levels (270 mg/dl versus serum level of 67 mg/dl), a low cholesterol level (10 mg/dl), and no identifiable cholesterol crystals. Microscopic examination of the fluid showed numerous neutrophils but no parasites or ova (1)(2)(3)(4). Gram staining revealed short rod-shaped bacteria, and cytology was negative for malignancy.…”
mentioning
confidence: 99%
“…The phylogenetic inference (Fig. 2) showed that both of the trichomonads found in the lungs of our patients were grouped in a separate clade with high levels of statistical support (a posterior probability of 0.96) with sequences of the new Tetratrichomonas species previously reported by Mantini et al (4). They were 99% identical, and they were distant from Tetratrichomonas gallinarum and other species of the Tetratrichomonas genus.…”
Section: Case Reportsmentioning
confidence: 71%